Moderate Effect of Financial Literacy during the Covid-19 Pandemic in Technology Acceptance Model on the Adoption of Online Banking Services - Akbar, Y. Rahmat; Zainal, Haznil; Basriani, Agustin; Zainal, Rahmi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research explored the factors that have a significant effect on the adoption of online banking services using the Technology Acceptance Model (TAM) theory, both directly and moderated by financial literacy. This quantitative study used a single cross-sectional research design to collect data from 100 respondents using Google Form. The collected data were analyzed using Structural Equation Modeling-Partial Least Square (PLS-SEM). The results showed that the perceived usefulness directly had a positive and significant impact on the adoption of online banking services. Likewise, the perception of ease of use shows that it directly has a positive and significant effect on the adoption of online banking services. The results also prove the moderating effect of financial literacy on the correlation between predictors and adoption of online banking services. This finding serves to inform managers and policymakers to design effective strategies by capturing customers' desire to use and experience using e-banking during the COVID-19 pandemic and economic globalization.